Theatre Archives' Outreach and Core Archival Functions - Harvey, Kathryn; Moosberger, Michael (Archivaria, 2007)
This paper outlines the evolution of the Dalhousie University Archives and Special Collections’ theatre archives in order to demonstrate how changing archival standards, technologies, and expectations have influenced our public service (provision of in-house access to materials) and outreach activities (the provision of services and research tools for specific audiences) and to suggest that the development of our award-winning digital resource From Artillery to Zuppa Circus: Recorded Memory of Theatre Life in Nova Scotia might serve as a model of how an archives can balance the immediate needs of the communities they serve – both donors and researchers – with a firm understanding of archives’ societal role, historical usage trends, and the dangers of focusing too narrowly on the short-term. Using Dalhousie University Archives and Special Collections’ theatre archives as a case study, the paper shows how outreach activities can fruitfully inform all aspects of holdings management from acquisition to description to public service without distracting from foundational principles and mandates. Indeed, the shortterm focus on outreach activities reaps long-term benefits from the improved visibility within archival and research communities. RÉSUMÉ Ce texte trace l’évolution des archives théâtrales conservées par les Dalhousie University Archives and Special Collections. Les auteurs veulent montrer comment les changements au niveau des normes archivistiques, des technologies et des attentes ont imprimé leur marque sur le service au public (les dispositions nécessaires pour la consultation des documents sur place) et les activités de relations externes (les dispositions nécessaires pour les services et les outils de recherche destinés à un public visé). De plus, ils suggèrent que le développement de leur projet de numérisation primé, From Artillery to Zuppa Circus: Recorded Memory of Theatre Life in Nova Scotia, pourrait servir de modèle pour explorer comment les archives peuvent considérer à la fois les besoins immédiats des communautés qu’elles desservent – autant les donateurs que les chercheurs – et la connaissance solide du rôle sociétal des archives, des tendances historiques de leur usage, et du danger de se concentrer trop étroitement sur les buts à court terme. En se servant des archives théâtrales conservées par les Dalhousie University Archives and Special Collections comme étude de cas, ce texte montre comment les activités de relations externes peuvent effectivement contribuer à une meilleure connaissance de tous les aspects de la gestion des collections, que ce soit l’acquisition, la description, ou le service au public, sans toutefois s’égarer des principes fondamentaux et des mandats. En effet, la concentration sur les activités de relations externes à court terme engendre des avantages à long terme grâce à la plus grande visibilité dans les milieux des archives et de la recherche.